ASSESSMENT OF SOCIO-ECONOMIC FEATURES CENTRAL REGIONAL MARKET OF HOUSING PROPERTY OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article assesses the socio-economic features of the Central region of Ukraine, within the limits of the proposed author’s vision to the territorial delineation of the country. The geographic, economic, demographic, social and other features are taken into account. In addition, the proposed studies are manifested in the indicators of the gross regional product, the housing stock of the region, the dynamics of acceptable in operation of the total area, capital investment in housing construction, indicators of residential maintenance of the population, dynamics of pricing on residential real estate, dynamics of the average cost per square meter residential real estate etc. The uniqueness of the research is connected with the substantiation of theoretical and practical hypotheses of the efficiency of functioning of regional markets of residential real estate, based on the empirical, socio-economic, and potential advantages of the region itself. As a result of the analysis, it was possible to substantiate the features of the competitive environment, as well as their influence on the pricing process and market demand. Ukraine is one of the largest in terms of population and area of Europe. The territory occupied by Ukraine is 603766 sq. Km, which is about 6 % of the whole territory of Europe. By volume of occupied territory Ukraine exceeds the indexes of such countries as Spain, France, Poland. The territorial extent of our state from the west to the east is no more than 1300 km, and from the northern part to the southern part it is about 890 km. The territory of Ukraine in the southern part is washed by the Black and Azov Seas; located at moderate latitudes and bordering the following countries: Poland, Slovakia, Hungary, Romania, Moldova, Belarus and the Russian Federation. The length of the border is about 6500 km, of which the sea passes – a little over a thousand. In general, the nature of economic and industrial territorial development of the state is clearly traced in the specifics of the regional economy of certain areas of its economy. Therefore, the relationship between the functioning of market processes in the region with the socio-economic potential and the economic assessment of the region itself is obvious and understandable. In this regard, as well as taking into account the author’s approach to regional distribution, the centrality of the analysis of social and economic factors of influence becomes central to the region. The results of studies on the formation and functioning of the residential real estate market in Ukraine have already been highlighted in the scientific papers of leading domestic and foreign scientists. The study of the market situation and socio-economic factors affecting the housing market in certain regions of the country was paid insufficient attention, which requires further and more in-depth research. The purpose of the article is to assess the socio-economic characteristics of the Central region of Ukraine and their impact on the regional market of residential real estate within the specified region. The main tasks should include: analysis of various components of socio-economic characteristics of the region; empirical substantiation of the hypothesis of the relationship of the main factors of the region’s development with the oblast (local) housing markets.
Keywords: socio-economic potential, regional gross product, urbanization, housing stock, competitiveness, capital investments, regionalization, market demand, pricing, price situation, regional market, central region, housing market of the central region